Scarti, tracce e frammenti: controarchivio e memoria dell'umano - VALDINOCI, FRANCESCA (Biblioteca di Studi di Filologia Moderna, 2019)
Scarti, tracce e frammenti: controarchivio e memoria dell'umano. Literature and art, increasingly interested in the dark side of production, now appear as a reservoir of fragments and waste of all sorts. The attraction towards scraps, conceived as anti-goods, testifies the existence of a parallel world where the myths of growth and productivity show their tragic face. Through different textualities and media, waste emerges as a testimony of a subversive marginality from which unexpected perspectives, which can undermine the established order, arise. The volume, using the image of waste, offers a hidden or marginalized counter history, which however 'returns' overbearingly in order to give contemporaneity its shapeless substance.